Oxetane cis- and trans-beta-amino-acid scaffolds from L-rhamnose by efficient S(N)2 reactions in oxetane rings; pseudoenantiomeric analogues of the antibiotic oxetin - Johnson, S; Jenkinson, S; Angus, D; Jones, J; Fleet, G; Taillefumier, C (2004)
An efficient multigram ring contraction of a 1,4-lactone 2-O-triflate derived from l-rhamnose - with retention of configuration in the ring closure - is the key step in the preparation of a series of oxetanes, which are pseudoenantiomeric analogues of the naturally occurring antibiotic oxetin, an oxetane cis-β-amino acid. Subsequent nucleophilic displacements of the corresponding triflates by azide proceed in consistently excellent yields, without any elimination, to provide syntheses of scaffolds for analogues of the antibiotic. © 2004 Elsevier Ltd. All rights reserved.